Implikasi Pemekaran Wilayah Kecamatan terhadap Pelayanan Publik di Kecamatan Congkar Kabupaten Manggarai Timur - Honorata Etralia Mardin; Saryono Yohanes; Agnes Doortji Rema (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This research aims to find out and analyze the implications of the expansion of sub-district areas on public services in Congkar District, East Manggarai Regency. This research is an empirical legal research supported by a socio-legal approach, a legislative approach and a conceptual approach using primary data and secondary data that are analyzed qualitatively descriptively. The results of the study show that (1) the expansion of Congkar District from Sambi Rampas District has had a real positive impact in the fields of administrative services, health, education, and infrastructure (2) the factors that hinder public services in Congkar District, East Manggarai Regency that hinder public services after the expansion are the factors of funds, infrastructure facilities and human resources.